The striking mimics between COVID-19 and malaria: A review - Konozy, Emadeldin Hassan E.; Osman, Makarim El-fadil M.; Ghartey-Kwansah, George; Abushama, Hind Mohamed (Frontiers in Immunology, 2022)
Objectives COVID-19 is a transmissible illness triggered by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Since its onset in late 2019 in Wuhan city of China, it continues to spread universally, leading to an ongoing pandemic that shattered all efforts to restrain it. On the other hand, in Africa, the COVID-19 infection may be influenced by malaria coinfection. Hence, in this review article, we aimed to give a comprehensive account of the similarities between COVID-19 and malaria in terms of symptoms, clinical, immunological, and molecular perspectives. Methodology In this article, we reviewed over 50 research papers to highlight the multilayered similarities between COVID-19 and malaria infections that might influence the ontology of COVID-19. Results Despite the poor health and fragile medical system of many sub-Saharan African countries, they persisted with a statistically significantly low number of COVID-19 cases. This was attributed to many factors such as the young population age, the warm weather, the lack of proper diagnosis, previous infection with malaria, the use of antimalarial drugs, etc. Additionally, population genetics appears to play a significant role in shaping the COVID-19 dynamics. This is evident as recent genomic screening analyses of the angiotensin-converting enzyme 2 (ACE2) and malaria-associated-variants identified 6 candidate genes that might play a role in malaria and COVID-19 incidence and severity. Moreover, the clinical and pathological resemblances between the two diseases have made considerable confusion in the diagnosis and thereafter curb the disease in Africa. Therefore, possible similarities between the diseases in regards to the clinical, pathological, immunological, and genetical ascription were discussed. Conclusion Understanding the dynamics of COVID-19 infection in Sub-Saharan Africa and how it is shaped by another endemic disease like malaria can provide insights into how to tailor a successful diagnostic, intervention, and control plans that lower both disease morbidity and mortality.